Compositional and immunobiological analyses of extracellular vesicles released by Candida albicans - Vargas, Gabriele; Rocha, Juliana D. B.; Oliveira, Debora Leite; Albuquerque, Priscila Costa; Frases, Susana; Santos, Suelen S.; Nosanchuk, Joshua Daniel; Gomes, Andre Marco Oliveira; Medeiros, Lia C. A. S.; Miranda, Kildare; Sobreira, Tiago J. P.; Nakayasu, Ernesto S.; et al. (Cellular microbiology, 2015)
Summary The release of extracellular vesicles (EV) by fungal organisms is considered an alternative transport mechanism to trans‐cell wall passage of macromolecules. Previous studies have revealed the presence of EV in culture supernatants from fungal pathogens, such as Cryptococcus neoformans, Histoplasma capsulatum, Paracoccidioides brasiliensis, Sporothrix schenckii, Malassezia sympodialis and Candida albicans. Here we investigated the size, composition, kinetics of internalization by bone marrow‐derived murine macrophages (MO) and dendritic cells (DC), and the immunomodulatory activity of C. albicans EV. We also evaluated the impact of EV on fungal virulence using the Galleria mellonella larvae model. By transmission electron microscopy and dynamic light scattering, we identified two populations ranging from 50 to 100 nm and 350 to 850 nm. Two predominant seroreactive proteins (27 kDa and 37 kDa) and a group of polydispersed mannoproteins were observed in EV by immunoblotting analysis. Proteomic analysis of C. albicans EV revealed proteins related to pathogenesis, cell organization, carbohydrate and lipid metabolism, response to stress, and several other functions. The major lipids detected by thin‐layer chromatography were ergosterol, lanosterol and glucosylceramide. Short exposure of MO to EV resulted in internalization of these vesicles and production of nitric oxide, interleukin (IL)‐12, transforming growth factor‐beta (TGF‐β) and IL‐10. Similarly, EV‐treated DC produced IL‐12p40, IL‐10 and tumour necrosis factor‐alpha. In addition, EV treatment induced the up‐regulation of CD86 and major histocompatibility complex class‐II (MHC‐II). Inoculation of G. mellonella larvae with EV followed by challenge with C. albicans reduced the number of recovered viable yeasts in comparison with infected larvae control. Taken together, our results demonstrate that C. albicans EV were immunologically active and could potentially interfere with the host responses in the setting of invasive candidiasis.